Spatial Analysis of Topography Effect in Eco Driving Level on Corridor VI BRT Semarang. (August 2019) - Rahayu, S; Basuki, Y; Putri, Y N
Abstract: Public transportation is important facilities to service the mobilization of citizen in urban activity. Bus Rapid Transit (BRT) is one of the modes considered suitable for developing cities such as Semarang. To ensure the sustainability of the BRT, good planning and operation and maintenance are required. In the operation of BRT eco driving behavior is believed to save fuel up to 13% and keep the fleet condition safe and reliable. This research is intended to know the behavior of the driver in operating the BRT. From driver behavior and onboard survey can be classified the level of eco driving the operation of BRT in Semarang. An eco driving level assessment was conducted on a sample of the BRT fleet. The analysis is done by making the level of eco driving using spatial analysis GIS. It divided into several levels that is high, medium and low. In the other hand, the topography is believed caused of the driver behavior. Furthermore, spatial analysis is done to map the areas that have variance slope. From the mapping results can be concluded which areas have low levels of eco driving and the slope characteristic. From these conclusions, recommendations for BRT performance improvement can be formulated.